SISTEM PEMBUKTIAN PADA TINDAK PIDANA SIBER DALAM HUKUM PIDANA FORMIL - Reza Moneta (2021)
The current development of information technology has had a huge impact. The development of globalization in the modern era can be seen in the development of technology and information which has a good effect, there are also some bad influences for humans. This development has caused and created a distance between the relations of all countries in the world to be without borders which resulted in rampant criminal acts in cyberspace. Cybercrime or also known as internet crime in cyberspace is a crime with a mode for perpetrators to seek profit from their victims. Cybercrime is very detrimental to its victims, so the state should protect the rights of victims affected by cybercrime cases. The perpetrators of these crimes are not limited in age, and they are also cross-border crimes in the territory. The approach applied in this research is juridical empirical. This approach examines the normative or juridical concept regarding the process and procedure of investigating cyber crime by Police investigators in accordance with the prevailing laws and regulations and their implementation in society, especially in Indonesia. This research explains the provisions in the prevailing laws and regulations, related to the realities in the field, then it analyzes by comparing the demand for ideal values in laws and regulations with the actual situation in the field. The results obtained show that Indonesia's judicial review of penalties under active criminal law is conducted in accordance with the Criminal Law and conventional criminal laws other than the Criminal Law.